2020
DOI: 10.1002/tpg2.20037
|View full text |Cite
|
Sign up to set email alerts
|

New tools for characterizing early brown stem rot disease resistance signaling in soybean

Abstract: Brown stem rot (BSR) reduces soybean [Glycine max (L.) Merr.] yield by up to 38%. The BSR causal agent is Phialophora gregata f. sp. sojae, a slow-growing, necrotrophic fungus whose life cycle includes latent and pathogenic phases, each lasting several weeks. Brown stem rot foliar symptoms are often misdiagnosed as other soybean diseases or nutrient stress, making BSR resistance especially difficult to phenotype. To shed light on the genes and networks contributing to P. gregata resistance, we conducted RNA se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 117 publications
0
6
0
Order By: Relevance
“…Glyma.13g256500 has been previously reported as a candidate gene for resistance to Phytophthora sojae (Li et al, 2016). While, Glyma.13g257100, was found to have a negative effect on the susceptibility to soybean mosaic virus when silenced (Liu and Whitham, 2013;McCabe and Graham, 2020). Both genes have been previously identified in association with disease resistance, and Glyma.13g256500 was specifically found to have resistance to a soil-borne fungal pathogen, similar to SDS.…”
Section: Discussionmentioning
confidence: 91%
“…Glyma.13g256500 has been previously reported as a candidate gene for resistance to Phytophthora sojae (Li et al, 2016). While, Glyma.13g257100, was found to have a negative effect on the susceptibility to soybean mosaic virus when silenced (Liu and Whitham, 2013;McCabe and Graham, 2020). Both genes have been previously identified in association with disease resistance, and Glyma.13g256500 was specifically found to have resistance to a soil-borne fungal pathogen, similar to SDS.…”
Section: Discussionmentioning
confidence: 91%
“…This disease is generally diagnosed as nutrient deficiency. To overcome misidentification of BSR, recently, McCabe and Graham [ 155 ] proposed a diagnostic approach based on genes and their network for fast and accurate identification. This approach may be helpful in management of this disease.…”
Section: Soybean Diseases and Molecular Developmentsmentioning
confidence: 99%
“…Further, the resistance was mapped to intervals ranging from 0.34 to 0.04 Mb, inclusive of BARCSOYSSR_16_1114 and BARCSOYSSR_16_1115 on chromosome 16. On the basis of these findings, it was concluded that only one gene is responsible for BSR resistance in soybean [ 155 ].…”
Section: Soybean Diseases and Molecular Developmentsmentioning
confidence: 99%
“…The annotations of the 21 DEGs in Figure 2 cluster L9 are associated with receptor like proteins (RLPs), leucine rich repeats (LRRs), and metal transport (Supplemental File 1: Table S1). This profile is noteworthy since in Arabidopsis, RLPs and LRRs regulate development, are known to confer resistance to a number of biological pathogens, and have been implicated in a number of abiotic stress tolerances [61][62][63]. Altered developmental regulation and defense responses are two hallmarks of the iron deficiency stress response in soybean.…”
Section: Genes Required For -P I Responsesmentioning
confidence: 99%